Determination of total phenolic content, total flavonoid content and antioxidant activity of various organic crude extracts of licuala spinosa leaves from Sabah, Malaysia - Mohammad Shaheen Khan; Samina Khan Yusufzai; Mohd Rafatullah; Mohd Sani Sarjadi; Mohd Razlan (2018)
In this study, the leaves of Licuala spinosa were used to determine the total phenolic and flavonoid content as well as antioxidant activity of different crude extracts. The samples were extracted successively with organic solvents such as hexane, chloroform and ethyl acetate respectively. The total phenolic content was determined by Folin-Ciocalteu’s assay. Chloroformcrude extract showed the highest total phenolic content (9.42± 0.06 mg GAE/g), followed by ethylacetate crude extract (8.91± 0.06 mg GAE/g) and hexane crude extract (6.78±0.26 mg GAE/g).The total flavonoid content was determined by Aluminium chloride colometric assay and expressedas QE equivalent. Chloroform crude extract showed the highest total flavonoid content (8.96 ± 0.21mg QE/g), followed by ethyl acetate crude extract (7.04 ± 0.02 mg QE/g) and hexane crude extract(3.05 ± 0.09 mg QE/g). The antioxidant activity of extracts were evaluated by 2,2-diphenyl-1-picyhydrazyl (DPPH) assay. In DPPH assay, IC50 values were used to determine the antioxidant potential of the sample. The lower the IC50 value, the higher the antioxidative property. Among allthe extracts, chloroform extracts exhibited higher DPPH radical scavenging activity with IC50 value of 0.032 mg /mL. BHT used as the positive control showed IC50 value of 0.089 mg/mL